2019
DOI: 10.1155/2019/7275289
|View full text |Cite
|
Sign up to set email alerts
|

Targeting INHBA in Ovarian Cancer Cells Suppresses Cancer Xenograft Growth by Attenuating Stromal Fibroblast Activation

Abstract: INHBA-encoded inhibin β A is a member of the transforming growth factor-β (TGF-β) superfamily. INHBA has been reported to be implicated in the progression of multiple types of cancer including ovarian cancer (OC). However, the mechanisms by which INHBA affects OC progression are not well-characterized. The aim of our study was to explore the prognostic value of INHBA for different stages and grades of OC and to identify the possible mechanisms by which INHBA promotes OC progression. Our results demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…A recent study showed that activin A overexpression promotes BC metastasis by activating Smad2 and inducing IL13Ra2 expression [10]. INHBA overexpression has been correlated with aggressive phenotype in different cancers, including colorectal cancer, lung adenocarcinoma, esophageal adenocarcinoma, ovarian cancer, and gastric cancer [11][12][13][14][15]. INHBA overexpression is also associated with a poor prognosis in gastric and lung cancer [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that activin A overexpression promotes BC metastasis by activating Smad2 and inducing IL13Ra2 expression [10]. INHBA overexpression has been correlated with aggressive phenotype in different cancers, including colorectal cancer, lung adenocarcinoma, esophageal adenocarcinoma, ovarian cancer, and gastric cancer [11][12][13][14][15]. INHBA overexpression is also associated with a poor prognosis in gastric and lung cancer [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…There are also reports in the literature that the effect of suppressing the development of colon cancer can be achieved by immunosuppression of CXCL3 [23][24][25][26][27]. INHBA has a significant relationship with the occurrence and development of gastric, esophageal, and ovarian cancers, and studies have reported that the immunosuppressive treatment of INHBA can reduce the rate of deterioration of gastric and ovarian cancers [28][29][30]. STC1 can promote the metastasis of colon cancer [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports in the literature that the effect of suppressing the development of colon cancer can be achieved by immunosuppression of CXCL3 [12][13][14][15][16]. INHBA has a significant relationship with the occurrence and development of gastric, esophageal, and ovarian cancers, and studies have reported that the immunosuppressive treatment of INHBA can reduce the rate of deterioration of gastric and ovarian cancers [17][18][19]. STC1OXTR, and UCN can promote the metastasis of colon cancer [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%